Solubility and Physical Stability Enhancement of Loratadine by Preparation of Co-Amorphous Solid Dispersion with Chlorpheniramine and Polyvinylpyrrolidone - Suknuntha, Krit; Khumpirapang, Nattakanwadee; Tantishaiyakul, Vimon; Okonogi, Siriporn (Pharmaceutics, 2023)
Loratadine (LRD), a non-sedating and slow-acting antihistamine, is often given in combination with short-onset chlorpheniramine maleate (CPM) to increase efficacy. However, LRD has poor water solubility resulting in low bioavailability. The aim of this study was to improve LRD solubility by preparing co-amorphous LRD-CPM. However, the obtained co-amorphous LRD-CPM recrystallized rapidly, and the solubility of LRD returned to a poor state again. Therefore, co-amorphous LRD-CPM solid dispersions using polyvinylpyrrolidone (PVP) as a carrier were prepared. The obtained solid dispersions were characterized using X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FT-IR). The solubility, dissolution, and mechanism of drug release from the LRD-CPM/PVP co-amorphous solid dispersions were studied and compared with those of intact LRD, LRD/PVP solid dispersions, and co-amorphous LRD-CPM mixtures. The results from XRPD and DSC confirmed the amorphous form of LRD in the co-amorphous solid dispersions. The FTIR results indicated that there was no intermolecular interaction between LRD, CPM, and PVP. In conclusion, the obtained LRD-CPM/PVP co-amorphous solid dispersions can successfully increase the water solubility and dissolution of LRD and extend the amorphous state of LRD without recrystallization.